Implementation Of Economic Production Quantity (EPQ) Method in Controlling Brick Production at UD SM Edi- Mardiana Serdang Bedagai - Rosmaida Zendrato; Manurung, Asima (Talenta Publisher, 2022)
achieving its goals, the company will face certain obstacles so that the companymust have good management. Because without good management the company will experiencea shortage of production (shortage) or excess production (over stock) which results inlosses for the company. UD. SM Edi Mardiana Serdang Bedagai is a business that producesbricks which is experiencing problems in the form of excess production inventory. Therefore,a policy is needed to control the amount of production by adjusting consumer needs so as notto cause losses for the company. One method that can be used is the Economic ProductionQuantity (EPQ) method which can determine the optimal production level, the optimal timeinterval to minimize inventory costs. From the results of calculations using the EPQ method,the optimal level of brick production for each production period is 4.326.589.75 seeds withan interval of 6,79 months and the total cost of procuring production with the EPQ method isRp313.532.065,9